Conducted emission investigation of infant incubator heating control mode - Khusnul Khotimah; Yoppy Yoppy; Muhammad Imam Sudrajat; Vera Permatasari; Elvina Trivida; Tyas Ari Wahyu Wijarnoko (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This paper investigates the effect of two different heating power control systems of infant incubators on their conducted emissions. Two infant incubators which respectively employ zero-crossing control mode and phase angle control mode are observed. The research was conducted by measuring conducted electromagnetic interference (EMI) from each infant incubator's power input. Measurements are conducted both during full power condition, while the incubator's compartment temperature is far away from the temperature setpoint, and during power chopping condition, while the compartment temperature reaches the steady-state set point. Method and limit of the measurement refer to CISPR 11. It is found that conducted emission higher than the standard CISPR 11 limit occurs during power chopping on phase angle control mode. This results from the sharp rise time of voltage delivered to the heater, around 220 ns for each chopping cycle.